Later gator : a Miss Fortune mystery - DeLeon, Jana (DeLeon, Jana. Miss Fortune series., 2016)
"A poacher is at work in Sinful, Louisiana, and Deputy Carter LeBlanc is hot on the trail of the outlaw, trying to apprehend him before the state gets wind of the crime and sends a game warden to take over his investigation. Unfortunately, he's hindered every step of the way by Sinful's current mayor and all-around horrible person, Celia Arceneaux, who wants nothing more than to drive Carter to resign. When a game warden turns up with evidence that implicates a relative of Gertie's, Carter is left with no choice but to arrest the boy, even though no one thinks he did it. With Carter under the watchful eye of Celia and the state, Fortune, Ida Belle, and Gertie decide to catch a poacher...before he gets away."--Back cover